Merging geometric documentation with materials characterization and analysis of the history of the holy aedicule in the church of the holy sepulchre in Jerusalem - Georgopoulos, Andreas; Lambrou, E.; Pantazis, G.; Agrafiotis, Panagiotis; Papadaki, A. I.; Kotoula, L.; Lampropoulos, K.; Delegou, E.; Apostolopoulou, M.; Alexakis, M.; Moropoulou, A. (My University, 2017)
The National Technical University of Athens undertook the compilation of an "Integrated Diagnostic Research Project and Strategic Planning for Materials, Interventions Conservation and Rehabilitation of the Holy Aedicule of the Church of the Holy Sepulchre in Jerusalem". This paper focuses on the work merging the geometric documentation with the characterization of materials, the identification of building phases and the diagnosis of decay and pathology through the use of analytical and non-destructive techniques. Through this integrated approach, i.e. through the documentation and characterization of the building materials, through the diagnosis of decay and pathology, through the accurate geometric documentation of the building and through the non-destructive prospection of its internal structure, it was feasible to identify the construction phases of the Holy Aedicule, identifying the remnants of the preserved earlier constructions and the original monolithic Tomb. This work, thus, demonstrates that the adoption of an interdisciplinary approach for integrated documentation is a powerful tool for a better understanding of monuments, both in terms of its structural integrity, as well as in terms of its state of preservation, both prerequisites for effective rehabilitation.
Keywords: Geomatics; Geometric documentation; Image based modelling; Materials; Non-destructive techniques; Terrestrial laser scanning